Taxonomic revision of the genus Eulimella (Gastropoda, Pyramidellidae) from Brazil, with description of three new species - Pimenta, Alexandre Dias; Santos, Franklin Noel Dos; Absalão, Ricardo Silva (Zootaxa, 2011)
A taxonomic revision of the pyramidellid genus Eulimella from Brazil was performed based on shell morphology. The holotype of Eulimella rudis Watson, 1886 is illustrated and compared to shells from the southeast Brazilian coast, this being the first confirmed record of this species after its original description. Eulimella smithii (Verrill, 1880), previously known from northern localities in the western Atlantic, is recorded from the southwestern Atlantic, along virtually the entire Brazilian coast; it is herein considered a distinct taxon from Eulimella unifasciata (Forbes, 1844), a very similar species from the eastern Atlantic, given the lack of data on development to consider an amphi-Atlantic distribution. Three new species are described: Eulimella torquata sp. nov., diagnosed by a constriction in the middle of each teleoconch whorl caused by a strong spiral furrow, producing a bilobed whorl profile; Eulimella cylindrata sp. nov., diagnosed by a large subcylindrical teleoconch; and Eulimella ejuncida sp. nov., characterized by its very slender shell, and small protoconch with only one whorl and with an “arc” shaped suture. The shells herein identified as Eulimella cf. calva from Brazil are conchologically identical to Eulimella calva Schander, 1994, from West Africa, but their taxonomic status should remain dubious because of lack of biological information to evaluate a possible amphi-Atlantic distribution pattern. All the species studied (except Eulimella ejuncida sp. nov.) have characteristic short microscopic axial threads organized in a spiral belt, varying in position and expression among species, but usually located in the middle of each teleoconch whorl or below the suture; this characteristic is also present in some species from the eastern Atlantic. Three South American species, originally or subsequently allocated in Eulimella, are herein considered as not belonging to this genus: Eulimella argentina Doello-Jurado, 1938; Eulimella bahiensis Castellanos, 1982; and Eulimella xenohyes (Melvill & Standen, 1912). The holotype of Eulimella lissa is illustrated with SEM micrographs.